Effect of Kinesiotaping in Reducing Low Back Pain in Pregnant Women: A Meta-Analysis - Handariati, Atik; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Pregnancy causes physiological changes that affect the musculoskeletal system and usually poses a risk of low back pain. This study aims to analyze the effect of kinesiotaping on reducing low back pain in pregnant women based on the results of a number of previous primary studies.Subjects and Method: This study uses a meta-analysis method with articles searched using the search keywords